2011
DOI: 10.1002/ana.22424
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological correlations in corticobasal degeneration

Abstract: Objective To characterize cognitive and behavioral features, physical findings and brain atrophy patterns in pathology-proven corticobasal degeneration (CBD) and corticobasal syndrome (CBS) with known histopathology. Methods We reviewed clinical and MRI data in all patients evaluated at our center with either an autopsy diagnosis of CBD (n=18) or clinical CBS at first presentation with known histopathology (n=40). Atrophy patterns were compared using voxel-based morphometry. Results CBD was associated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

32
380
2
6

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 381 publications
(437 citation statements)
references
References 51 publications
32
380
2
6
Order By: Relevance
“…Clinicopathologic correlation studies confirm that overlapping clinical phenotypes are associated with AD and FTLD spectrum pathology in multiple domains of cognition. 17,24,25 Corticobasal syndrome often due to FTLD spectrum pathology and posterior cortical atrophy often due to AD have overlapping visuospatial features; nonfluent/agrammatic primary progressive aphasia associated with FTLD spectrum pathology and logopenic primary progressive aphasia associated with AD may have overlapping language difficulties; patients with behavioral variant frontotemporal dementia and patients with AD may present with behavioral difficulty, an executive disorder, or an episodic memory deficit. Therefore, there is an urgent need to im- prove diagnostic accuracy in a quantitative manner that does not rely on clinical features in order to screen patients for clinical trials involving diseasemodifying agents.…”
Section: Resultsmentioning
confidence: 99%
“…Clinicopathologic correlation studies confirm that overlapping clinical phenotypes are associated with AD and FTLD spectrum pathology in multiple domains of cognition. 17,24,25 Corticobasal syndrome often due to FTLD spectrum pathology and posterior cortical atrophy often due to AD have overlapping visuospatial features; nonfluent/agrammatic primary progressive aphasia associated with FTLD spectrum pathology and logopenic primary progressive aphasia associated with AD may have overlapping language difficulties; patients with behavioral variant frontotemporal dementia and patients with AD may present with behavioral difficulty, an executive disorder, or an episodic memory deficit. Therefore, there is an urgent need to im- prove diagnostic accuracy in a quantitative manner that does not rely on clinical features in order to screen patients for clinical trials involving diseasemodifying agents.…”
Section: Resultsmentioning
confidence: 99%
“…Other criteria that exclude a CBD diagnosis are the autonomic disturbances, the emergence of early vertical gaze palsy and the presence of structural damage on imaging studies [7]. It is a matter of conflict whether early dementia belongs to the exclusion criteria, as occasionally it appears as the prominent symptom of the disease [8,12,13,29]. The main features of cognitive decline include apraxia and especially ideomotor apraxia and nonfluent aphasia.…”
Section: Discussionmentioning
confidence: 99%
“…In CBD dementia, neuropsychological deficits are reflected by functional criteria and not the white matter lesions of MRI as long as atrophy has not occurred [26][27][28]. However, post-mortem studies have demonstrated that frontal lobe involvement is characteristic of CBD, as frequently frontal symptoms such as behavioral and cognitive disorders predominate at the disease initial stages [12,13,29].…”
Section: Discussionmentioning
confidence: 99%
“…For example, cases of CBS have shown Alzheimer pathology, Lewy body disease, or progressive supranuclear palsy at autopsy. 5,6 CBS classically begins as a unilateral akinetic-rigid disorder with associated localizing cortical findings that may include cortical sensory loss, alien limb phenomenon, and pyramidal findings. Apraxia is frequently associated with CBS.…”
mentioning
confidence: 99%